Integrasi Analytic Network Processing dan Technique for Order Preference by Similarity to Ideal Solution sebagai Perancangan Strategi dalam Meningkatkan Daya Saing pada Perguruan Tinggi XYZ - Achmad Bilal Hamdani; Rony Prabowo (Jurnal Syntax Admiration, 2024)
Seizing consumer preferences is crucial for organisations amidst increasingly intense competition. Success in this competition depends on the product's ability to fulfil customer needs and wants. All universities in Indonesia are faced with similar challenges, namely how to formulate and plan for their future in the face of ever-evolving societal changes. To respond to this challenge, it is necessary to develop a strategy that increases the competitiveness of universities. From the literature review, the criteria for increasing the competitiveness of the XYZ Institute are obtained, namely, product, price, place, promotion, people, process, physical evidence. Each criterion, through the brainstorming, is broken down into sub-criteria. The process to determine the right strategy design can be done in many methods, and among them are the ANP (Analytical Network Process) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. The results of weighting the criteria using the ANP method using the Super Decisions software are then ranked using the TOPSIS method. The result is that the three best strategies are to improve the Product, namely, Alumni Quality (score 0.713397108), followed by improving Promotion, namely, the Institute accreditation score (score 0.709584147) and the People aspect, namely, student input selection (score 0.704887758).